2015
DOI: 10.4103/2321-1407.155837
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating condylar position in different skeletal malocclusion patterns: A cephalometric study

Abstract: Context The cranial base and variations in its morphology affect the anterior-posterior positioning of jaws causing changes in the glenoid fossa and condylar position. Aims To evaluate the condylar position in patients with different skeletal sagittal malocclusion patterns. Materials and Methods Pretreatment lateral cephalometric radiographs of 112 subjects (both males and females) were categorized into three classes (Class I, Class II, Class III) based on their ANB angulation and studied for N-S-Ar (saddl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 20 publications
1
8
1
Order By: Relevance
“…In the current study, the articular angle was similar among the different AP skeletal relationships. This was in agreement with Hegde et al 27 Rodriguez-Cardenas et al, 28 on the other hand, found that articular angle was increased in the Class I skeletal relationship compared with other skeletal relationships. The differences between the current results and the previous studies could have been related to the nature of the samples and included age groups.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, the articular angle was similar among the different AP skeletal relationships. This was in agreement with Hegde et al 27 Rodriguez-Cardenas et al, 28 on the other hand, found that articular angle was increased in the Class I skeletal relationship compared with other skeletal relationships. The differences between the current results and the previous studies could have been related to the nature of the samples and included age groups.…”
Section: Discussionsupporting
confidence: 92%
“…They did not find condylar position with respect to glenoid fossa. 8 Wigal et al did his study on subjects with Class II malocclusion treated with herbst appliance found significant positioning of condyle and glenoid fossa in compare to control group. 9 Vankadara et al did his study on CBCT and states that centric position is most common position of condyle and 4,7 position is the most common according to Gelb's 4,7 grid.…”
Section: Discussionmentioning
confidence: 96%
“…In present study we found that for Group I condyle was positioned normally (4,7) in 86.66% of subjects and was displaced posteriorly (5,8) 13.33% of subjects. For Group II condyle was displaced posteriorly (5,8) in 86.66% of subjects and in normal position (4,7) for remaining subjects. For Group III subjects condyle was again found in posteriorly displaced 66.66% of subjects and normally positioned in rest.…”
Section: Discussionmentioning
confidence: 96%
“…Some studies have reported no significant difference between the condylar position in Class I and Class III subjects, 7,8 while others have reported the difference. 5,9 These discrepancies might be due to differences in measuring technique and parameters used to assess the condylar position.…”
Section: 7-9mentioning
confidence: 97%